Dinamika Hukum Pertahanan Dan Keamanan Negara Dalam Konteks Globalisasi: Tantangan Dan Prospek Di Abad Ke-21 - Muhammad Anwar Ibrahim; Irwan Triadi (Hakim, 2024)
The ever-evolving global landscape, marked by rapid technological advancements and increasingly complex security threats, places national defense and security law at the forefront of safeguarding a nation's stability, sovereignty, and safety. This research delves into the multifaceted dimensions of defense and security law, aiming to comprehend, evaluate, and analyze legal issues pertinent to national defense and security. Employing a juridical analysis methodology, this study focuses on an in-depth review of existing legal regulations, encompassing a spectrum from constitutional provisions to statutes, governmental regulations, relevant court decisions, and international agreements associated with national defense and security. The juridical analysis comprises several key components. Firstly, an extensive exploration of legal theories in defense and security as elucidated by experts in the field through literature review provides foundational theoretical insights. Secondly, a meticulous examination of legal documents unveils the intricacies of laws governing defense and security, shedding light on fundamental aspects crucial to the nation's safety. Additionally, comparative legal analysis across multiple jurisdictions elucidates the disparities, commonalities, and implementations of laws in defense and security contexts globally. Furthermore, the study of concrete cases offers a practical understanding of legal application in real-world defense and security scenarios. The methodological approach involves an exhaustive scrutiny of legal texts and a meticulous interpretation of pertinent legal aspects, aiming to identify weaknesses within the existing legal framework. From these evaluations, suggestions for enhancements or developments will be proposed to augment the effectiveness and adaptability of laws pertaining to national defense and security. This research endeavors to contribute substantively to the comprehension, advancement, and reform of the domain.